Proceedings of the 28th IEEE Conference on Decision and Control
DOI: 10.1109/cdc.1989.70374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of suboptimal Kalman tracking algorithms

Abstract: The standard Kalman filter has been applied extensively to the trackingof non-maneuveringtargets. Although thisfilter tracks these targets accurately it requires a heavy computational burden. This paper studies several suboptimal Kalman filtering schemes which require less computational burden than the standard Kalman filter while yielding nearly optimal performance during both transient and steady-state filtering. It is shown that these suboptimal filters are viable alternatives to the standard Kalman filtel:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…An analysis of Baheti's filter [9] has demonstrated that his algorithm, as described in [2], will only track accurately during steady State conditions. Baheti's algorithm calculates the Kalman gain using equation (4).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…An analysis of Baheti's filter [9] has demonstrated that his algorithm, as described in [2], will only track accurately during steady State conditions. Baheti's algorithm calculates the Kalman gain using equation (4).…”
mentioning
confidence: 98%
“…Rather than use the standard Kalman filter, a computationally more efficient filter, which is a modified version of the filter presented by Baheti in [ 11, was selected for implementation [9].…”
mentioning
confidence: 99%